2018
DOI: 10.1007/s12035-018-1192-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Pathways in Mutant Rhodopsin Rat Models Identifies Genotype-Specific Targets Controlling Retinal Degeneration

Abstract: Retinitis pigmentosa (RP) is a group of inherited neurological disorders characterized by rod photoreceptor cell death, followed by secondary cone cell death leading to progressive blindness. Currently, there are no viable treatment options for RP. Due to incomplete knowledge of the molecular signaling pathways associated with RP pathogenesis, designing therapeutic strategies remains a challenge. In particular, preventing secondary cone photoreceptor cell loss is a key goal in designing potential therapies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 60 publications
4
28
0
Order By: Relevance
“…Although photoreceptor death by apoptosis has been reported in models of retinal degeneration [ 7 , 8 , 11 , 12 ], there is growing evidence that caspase-independent cell death mechanisms are also involved in many blinding diseases, including RP. Indeed, some recent studies have suggested that these alternative mechanisms may be the dominant modes of cell death in RP [ 13 , 14 ]. Several forms of regulated necrosis have recently been described; including necroptosis, ferroptosis, pyroptosis and parthanatos [ 15 , 16 ].…”
Section: Cell Death Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although photoreceptor death by apoptosis has been reported in models of retinal degeneration [ 7 , 8 , 11 , 12 ], there is growing evidence that caspase-independent cell death mechanisms are also involved in many blinding diseases, including RP. Indeed, some recent studies have suggested that these alternative mechanisms may be the dominant modes of cell death in RP [ 13 , 14 ]. Several forms of regulated necrosis have recently been described; including necroptosis, ferroptosis, pyroptosis and parthanatos [ 15 , 16 ].…”
Section: Cell Death Mechanismsmentioning
confidence: 99%
“…Initiation of this process can occur by activation of cell death receptors, toll-like receptors, interferons or DNA damage sensors. Necroptosis has been implicated in both rod and cone degeneration in animal models of RP in several recent studies [ 14 , 20 , 21 , 22 ], discussed further below.…”
Section: Cell Death Mechanismsmentioning
confidence: 99%
“…Several authors have proposed the upregulation of caspase 3/8 activities and mitochondrial cytochrome C release in RP models like transgenic S334ter rats, tubby mice, rds mice, etc. [76][77][78][79] However, other caspase 3-independent mechanisms have been reported for rod cell death in rd mice or P23H rats. 80,81 Double labeling with TUNEL and cleaved caspase 3 indicated that degenerating photoreceptors (TUNEL positive cells) were not cleaved-caspase 3 positive cells (an early event of apoptosis) at this age.…”
Section: A Single Dose Of Intravitreal Adalimumab Reduced Nlrp3 Infmentioning
confidence: 99%
“…For instance, Viringipurampeer et al proposed that the primary driver of early rod cell death was a caspase-dependent process, whereas cone cell death occurred through RIPK3-dependent necroptosis in the transgenic S334ter rhodopsin. 77 The same authors described that primary necroptosis was involved in early rod cell death, whereas cone cell loss occurred through inflammasome activation in P23H rats. 77 Murakami et al 47 suggested that apoptosis occurred early, during rod degeneration but, RIPK3mediated necroptosis was responsible for cone degeneration at later stages (at P35 or later) in rd10 mice.…”
mentioning
confidence: 97%
See 1 more Smart Citation